Ocena funkcjonujących systemów zarządzania jakością - nadzór nad dokumentami i zapisami - Wierzbic, Arkadiusz (The evaluation of quality management systems - control of documents and records, 2005)
Control of documents and control of records are the most basic requirements of EN ISO 9001:2000. The research conducted in fifty organizations operating in Poland provided data for analysis of fulfilling these requirements. All visited organizations have implemented and certified quality management system according to EN ISO 9001:2000. The proper implementation of even very simple solutions in controlling documents and records provides an order and easy access to information from inside the organization. In more advanced solutions based on specialized software there are additional benefits like ability to faster analyzing of data and faster decision making. Such systems are proper for large or medium companies. The research shows that tire implementation of control of documents based on software solutions is not so complicated, but control of records is much more difficult and is a challenge even for companies operating in the area of informatics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 384-390